G protein β3 subunit 825T allele and its potential association with obesity in hypertensive individuals - Siffert, Winfried; Naber, Christoph Kurt; Walla-Friedel, Maria; Ritz, Eberhard (Journal of hypertension, 1999)
The 825T allele of the G protein β3 subunit is associated with hypertension in Caucasians. To generate a novel hypothesis regarding the underlying mechanisms, we examined for a potential association of the 825T allele with obesity in hypertension.